Analisis Pembentukkan Portofolio Optimal pada Pengelolaan Keuangan Haji - Asep Saepullah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The Hajj Financial Management Agency needs to increase its profitability because every year it must pay the subsidy for the Hajj Pilgrimage Implementation Costs for each regular pilgrim who will depart. The source of funds for this subsidy comes from the Value Benefit or yield or return from the management of funds through placements and investments. This study aims to determine the optimal portfolio in the management of hajj funds from several portfolio scenarios. This research uses a quantitative approach through the calculation of returns, expected returns, portfolio risk, and variance matrix, followed by calculations with the linear programming method using Excel Solver to determine the optimal portfolio scenario with the Markowitz approach. In obtaining data for the research process, secondary data is used, obtained from several relevant sources for the period 2020–2024 on a monthly basis with a total of 60 (sixty) samples. The data obtained include the rate of return on Islamic bank deposits, the rate of return on State Sharia Securities, the rate of return on murabaha financing, and gold price movement data. The results of this study recommend a moderate scenario (without regulatory limits) with a portfolio composition of 20% Islamic Bank Deposits, 47.35% State Sharia Securities, 32.65% Murabaha Financing, and 0.00% Gold, in which this portfolio composition can generate an expected return of 7.29% and a risk of 0.34%.